Incidence of Colon Ciliate Buxtonella sulcata in Cattle at Hisar, Haryana - Khirbat, Richa; Vohra, Sukhdeep; Gera , Sandeep; Pal, Kulender (International Journal of Livestock Research, 2019)
The present study was conducted to detect the incidence of Buxtonella sulcata infection in Cattle at Hisar, Haryana. A total of 60 faecal samples from Shri Krishan Gaushala and Go Anusandhan Kendra, Kabrel, Hisar (n = 30) and Haryana Kurukshetra Gaushala, Hisar, (n = 30) were examined. The results revealed an overall infection of 45% in the examined animals. A significant difference (p<0.01) in the incidence of infection was observed between two Gaushalas. The prevalence of B. sulcata also showed a significant (P<0.01) difference between the diarrhoeic and normal faeces. The sedimentation method of examination of cyst showed a significant (P<0.01) higher number of positive animals as compared to floatation method using saturated magnesium sulphate solution. Addition of Lugol’s Iodine further enhanced the visibility of the protozoan cyst. The examination of sediment also revealed the eggs of amphistomes in one of the cattle of Haryana Kurukshetra Gaushala, Hisar.